Intraductal Papillary Mucinous Neoplasm Complicated by Formation of Fistulous Tracts: A Case Report with Imaging and Anatomopathological Correlation - Cartucho,Rita (2024)
Abstract Intraductal Papillary Mucinous Neoplasms are pancreatic cystic lesions characterized by a dilated main pancreatic duct and/or dilated branch ducts with papillary projections composed of dysplastic mucinous epithelium. A notable complication associated with IPMNs is the occurrence of fistulization into adjacent organs. In this article, we present one case of IPMN complicated by two gastropancreatic fistulas. We aim to review the latest literature about fistulas frequency and prognosis, which organs are affected the most, the mechanisms for fistula formation and possible methods that might help in the management of this complication.